Immigration Legal Politics Supporting IKN Development as a Global Economic Growth Hub - Komang Trisna Diatmika; Faisal Santiago (al-Battar: Jurnal Pamungkas Hukum, 2025)
The development of the Indonesian Capital City (IKN) as a national strategic project is aimed not only at relocating the center of government but also at establishing a new hub of global economic growth. This article aims to analyze the role of immigration legal politics in supporting investment inflows, the mobility of foreign experts, and diaspora participation in the development of the IKN. This study employs normative legal research using a statutory and conceptual approach, examining Law Number 6 of 2011 on Immigration, Law Number 3 of 2022 in conjunction with Law Number 21 of 2023 concerning the IKN, and Regulation of the Minister of Law and Human Rights Number 22 of 2023 on Visas and Residence Permits. The findings indicate that Indonesia’s immigration policy has undergone a paradigm shift from a purely supervisory function toward a selective and incentive-based approach that supports national development objectives. Instruments such as the Golden Visa, Limited Stay Permit (ITAS), and Permanent Stay Permit (ITAP) provide legal certainty for foreign investors, professionals, and the Indonesian diaspora, thereby facilitating capital inflows, technology transfer, and global connectivity for the IKN. However, the study also identifies challenges, including the potential misuse of residence permits, regulatory overlap between central authorities and the IKN Authority, and the need to balance economic openness with the protection of national sovereignty and local labor. This article concludes that the establishment of specific and harmonized immigration regulations for the IKN is essential to ensure legal certainty, effective supervision, and policy coherence. An adaptive and selective immigration legal strategy is crucial for positioning the IKN as a sustainable, competitive, and globally integrated economic center while safeguarding Indonesia’s national interests.